Study on soil reinforcement param in deep foundation pit of marshland metro station. Issue 11 (November 2019) - Wang, Wei; Han, Zhao; Deng, Jun; Zhang, Xinyuan; Zhang, Yanfei
Abstract: In this paper, the reinforcement method outside the deep foundation pit of a subway station in marshland under a high water level was proposed, and the reinforcement parameters were studied. The influence of reinforcement measures outside the deep foundation pit on deformation and the anti-overturning stability coefficient of the diaphragm wall under high water levels was analyzed. According to the economic law of diminishing marginal returns, the grouting reinforcement parameters were analyzed and optimized. The effects of different reinforcement measures on the safety control of deep foundation pits was analyzed based on field-measured data. The results show that the change in the water level has a significant impact on the stability of the foundation pit, and it is necessary to adopt reinforcement measures for the foundation pit at 10 m below the surface; the change in the reinforcement depth has a more significant impact on the stability of the foundation pit; and the optimized reinforcement parameters can reduce the grouting volume by 45%. Abstract : Civil engineering; Geotechnical engineering; Soil engineering; Construction engineering; Foundation engineering; Structural analysis; Structural health monitoring; High water level; Subway station; Deep foundation pit; Soil reinforcement outside the excavation; Stability control; Parameter optimization